2012
DOI: 10.1002/cbdv.201200073
|View full text |Cite
|
Sign up to set email alerts
|

Correlating CH Bond Cleavage with Molybdenum Reduction in Xanthine Oxidase

Abstract: We have performed a computational study of substrate CÀH bond activation in enzymes of the XO family. The CÀH H-atom for all XO substrates studied is transferred to the terminal sulfido at the transition state with near neutral charge, and this is consistent with both Mo¼S p ! CÀH s* and CÀH s ! Mo¼S p* donorÀacceptor interactions activating the CÀH bond. A CÀH bond scission and Mo reduction appear to be highly correlated along the reaction coordinate for all XO substrates studied, with Mo reduction being a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…This high barrier is in accordance with the experimental observation that the desulfo form of XO is inactive, , although kinetic, spectroscopic, and crystallographic studies indicate that the related aldehyde oxidoreductase enzyme is active without the sulfido group . Kirk and co-workers have emphasized the role of the sulfido ligand for the proper electronic structure of the transition state for the hydride-transfer reaction. , Thus, we can conclude that the XO active site is carefully designed to make all three steps in the reaction mechanism possible: a proper acidity to make the initial proton transfer possible, a favorable net charge to enable the oxy transfer, and again a proper acidity to make the hydride transfer feasible. No native or designed enzyme model combines these properties as well as the XO model.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…This high barrier is in accordance with the experimental observation that the desulfo form of XO is inactive, , although kinetic, spectroscopic, and crystallographic studies indicate that the related aldehyde oxidoreductase enzyme is active without the sulfido group . Kirk and co-workers have emphasized the role of the sulfido ligand for the proper electronic structure of the transition state for the hydride-transfer reaction. , Thus, we can conclude that the XO active site is carefully designed to make all three steps in the reaction mechanism possible: a proper acidity to make the initial proton transfer possible, a favorable net charge to enable the oxy transfer, and again a proper acidity to make the hydride transfer feasible. No native or designed enzyme model combines these properties as well as the XO model.…”
Section: Resultssupporting
confidence: 84%
“…77 Kirk and coworkers have emphasized the role of the sulfido ligand for the proper electronic structure of the transition state for the hydride-transfer reaction. 78,79 Thus, we can conclude that the XO active site is carefully designed to make all three steps in the reaction mechanism possible: a proper acidity to make the initial proton transfer possible, a favorable net charge enable the oxy transfer, and again a proper acidity to make the hydride transfer feasible. No native or designed enzyme model combines these properties as well as the XO model.…”
Section: The Dmsor-xan and So-xan Reactionsmentioning
confidence: 99%
“…The key aspect that dictates the plane in which the chemistry occurs is the presence of a thiolate or sulfido ligand adjacent to the catalytically labile oxygen, and the availability of an equatorial in-plane S π bond that can accept the departing hydride from substrate. 275 …”
Section: The Sulfite Oxidase Familymentioning
confidence: 99%
“…We have shown that the degree of Mo reduction along the reaction coordinate is strongly correlated to the degree of C substrate -H bond cleavage for a variety of XO/XDH substrates, including lumazine. [48] A longer C-H distance observed at the TS was shown to correlate with a greater percentage of Mo reduction at the TS. [48] We define the percent Mo reduction at the TS as the %Mo(xy) character in the TS redox orbital divided by the %Mo(xy) character in the reduced IM2 E-P complex.…”
Section: Resultsmentioning
confidence: 99%
“…[48] A longer C-H distance observed at the TS was shown to correlate with a greater percentage of Mo reduction at the TS. [48] We define the percent Mo reduction at the TS as the %Mo(xy) character in the TS redox orbital divided by the %Mo(xy) character in the reduced IM2 E-P complex. We find that the Mo(xy) character present in the TS redox orbital is ~28%, while that in the Mo(IV)-4-TV product HOMO is ~73%.…”
Section: Resultsmentioning
confidence: 99%